MdWRKY75e enhances resistance to Alternaria alternata in Malus domestica. (11th October 2021) - Hou, Yingjun; Yu, Xinyi; Chen, Weiping; Zhuang, Weibing; Wang, Sanhong; Sun, Chao; Cao, Lifang; Zhou, Tingting; Qu, Shenchun
Abstract: The Alternaria alternata apple pathotype adversely affects apple ( Malus domestica Borkh.) cultivation. However, the molecular mechanisms underlying enhanced resistance to this pathogen in apple remain poorly understood. We have previously reported that MdWRKY75 expression is upregulated by A. alternata infection in 'Sushuai' apples. In this study, we discovered that overexpression of MdWRKY75e increased the resistance of transgenic apple lines to A. alternata infection, whereas silencing this gene enhanced susceptibility to A. alternata infection. Furthermore, we found that MdWRKY75e directly binds to the MdLAC7 promoter to regulate the biosynthesis of laccase and increase the biosynthesis of lignin during A. alternata infection. Moreover, the thickening of the cell wall enhanced the mechanical defense capabilities of apple. In addition, we found that jasmonic acid remarkably induced MdWRKY75e expression, and its levels in transgenic apple lines were elevated. These results indicate that MdWRKY75e confers resistance to the A. alternata apple pathotype mainly via the jasmonic acid pathway and that pathogenesis-related genes and antioxidant-related enzyme activity are involved in the disease resistance of MdWRKY75e transgenic plants. In conclusion, our findings provide insights into the importance of MdWRKY75e for resistance to A. alternata infection in apples.